Variations in Gut Microbiome are Associated with Prognosis of Hypertriglyceridemia-Associated Acute Pancreatitis - Xiaomin Hu; Liang Gong; Ruilin Zhou; Ziying Han; Li Ji; Yan Zhang; Shuyang Zhang; Dong Wu (Biomolecules, 2021)
Hypertriglyceridemia-associated acute pancreatitis (HTGAP) is linked with increased severity and morbidity. Intestinal flora plays an important role in the progression of acute pancreatitis (AP). However, pathogenetic association between gut microbiota and HTGAP remains unknown. In this study, we enrolled 30 HTGAP patients and 30 patients with AP that is evoked by other causes. The V3–V4 regions of 16S rRNA sequences of the gut microbiota were analyzed. Clinical characteristics, microbial diversity, taxonomic profile, microbiome composition, microbiological phenotype, and functional pathways were compared between the two groups. Our results showed that the HTGAP group had a higher proportion of severe AP (46.7% vs. 20.0%), organ failure (56.7% vs. 30.0%), and a longer hospital stay (18.0 days vs. 6.5 days). HTGAP group also had poorer microbial diversity, higher abundances of Escherichia/Shigella and Enterococcus, but lower abundances of Dorea longicatena, Blautia wexlerae, and Bacteroides ovatus as compared with non-HTGAP group. Correlation analysis revealed that gut bacterial taxonomic and functional changes were linked with local and systemic complications, ICU admission, and mortality. This study revealed that alterations of gut microbiota were associated with disease severity and poor prognosis in HTGAP patients, indicating a potential pathophysiological link between gut microbiota and hypertriglyceridemia related acute pancreatitis.